Kettlebell conditioning 4-phase bodybell training system with Australia's body coach : plus 25 bonus medicine ball training drills - Collins, Paul, 1970- (The body coach, 2011)
Every good exercise program starts with a method by which training principles are based upon. In Kettlebell Conditioning, Coach Collins has developed the 4-Stage BodyBell(R) Training SystemA' that allows you to learn the basic strength and swing pattern drills before more complex power orientated movement patterns. The unique shape of the kettlebell challenges the whole body as the hand, arm, shoulder and core region controls the displacement of weight and counteraction of muscles with each movement.